Lithium Ion Battery Thermal Management System Using Optimized Fuzzy Controller - Hannan M.A.; Young Y.S.; Hoque M.M.; Ker P.J.; Uddin M.N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Algorithms; Automobile cooling systems; Battery management systems; Battery Pack; Controllers; Fuzzy logic; Fuzzy systems; Ions; Particle swarm optimization (PSO); Robust control; Temperature control; Thermal management (electronics); Traffic signals; Battery performance; Battery thermal managements; Fuzzy controllers; Fuzzy logic controllers; Heating and cooling systems; Irreversible capacity loss; Thermal management systems; Uniform temperature; Lithium-ion batteries